2010
DOI: 10.1038/onc.2010.434
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 cleaves XIAP in a positive feedback loop to sensitize melanoma cells to TRAIL-induced apoptosis

Abstract: Successful treatment of melanoma is still challenging, because metastasis remain chemoresistant and radioresistant. Accordingly, combinational treatments involving death ligands are mandatory. In a recent study from our lab, the majority out of 18 melanoma cell lines remained resistant against treatment with the death ligand TRAIL (tumor necrosis factor related apoptosis inducing ligand). Resistance was shown to be mainly due to incomplete processing of caspase-3 into catalytically inactive p21 by binding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 52 publications
5
64
0
Order By: Relevance
“…P0018A; Beyotime Institute of Biotechnology). Subsequent to incubation with the indicated TRAIL treatment doses (20,40,60, 80 and 100 ng/ml) for various lengths of time (4,8,12,18 and 24 h), cells were harvested, and the cell pellets were suspended in 500 µl binding buffer [10 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (pH 7.4), 140 mM NaCl, 1 mM MgCl 2 , 5 mM KCl and 2.5 mM CaCl 2 ] at a density of 1x10 6 cells⁄ml. Samples were incubated with 1 µl annexin V-fluorescein isothiocyanate (FITC) and 5 µl PI for 5 min at room temperature in the dark and measured on a FACSort flow cytometer (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P0018A; Beyotime Institute of Biotechnology). Subsequent to incubation with the indicated TRAIL treatment doses (20,40,60, 80 and 100 ng/ml) for various lengths of time (4,8,12,18 and 24 h), cells were harvested, and the cell pellets were suspended in 500 µl binding buffer [10 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (pH 7.4), 140 mM NaCl, 1 mM MgCl 2 , 5 mM KCl and 2.5 mM CaCl 2 ] at a density of 1x10 6 cells⁄ml. Samples were incubated with 1 µl annexin V-fluorescein isothiocyanate (FITC) and 5 µl PI for 5 min at room temperature in the dark and measured on a FACSort flow cytometer (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Friboulet et al (19) showed that EBV-positive NPC cell lines expressed increased levels of inhibitor of apoptosis proteins (IAPs), which have anti-apoptotic functions. Additionally, X-linked inhibitor of apoptosis protein (XIAP) is a member of the IAP family that inhibits caspases and induces TRAIL resistance (20).…”
Section: Introductionmentioning
confidence: 99%
“…As a direct inhibitor of these caspases, XIAP has been detected on the apoptosome (Bratton et al 2001(Bratton et al , 2002. In a recent study of melanoma cell lines, XIAP was also subject to caspase cleavage in a positive feedback loop that reduces caspase inhibition and XIAP levels through proteasomal degradation (Hornle et al 2011). Although XIAP is the best-characterized vertebrate member of the IAP family with regard to direct binding and inhibition of caspases, one recent study showed that cIAP1 can specifically block apoptosis downstream of cytochrome c release by binding to and inhibiting active caspase-9 within the apoptosome, precluding downstream activation of procaspase-3 (Burke et al 2010).…”
Section: Iapsmentioning
confidence: 99%
“…Activation of NF-kB enhances the expression of antiapoptotic proteins such as inhibitor of apoptosis proteins (IAP), X-linked IAP (XIAP), Bcl-2, Bcl-xL, and c-FLIP (4). Human IAP proteins, including cIAP-1, cIAP-2, XIAP, are known to inhibit apoptosis by inhibiting effector caspases, caspase-7 and -3 (5).…”
Section: Introductionmentioning
confidence: 99%